2023
DOI: 10.1186/s12912-022-01156-x
|View full text |Cite
|
Sign up to set email alerts
|

Key determinates of job satisfaction for acute care nurse practitioners in Taiwan

Abstract: Background Taiwan is a super-aged society, and the shortage of hospital doctors; nurse practitioners (NPs) became vital healthcare providers to fulfill the healthcare demands of the population. The purpose of this study was to explore the key determinates of job satisfaction for NPs in acute care practices using significant practice variables, such as empowerment and burnout. Methods Participants of this descriptive survey study were recruited from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
1
0
1
Order By: Relevance
“…Contrary to a previous study (Suresh and Kodikal, 2015), this study showed age group had no influence on job satisfaction (p>0.05). In terms, of gender majority of the respondents were female (mean rank=350.96) and moderate level of job satisfaction comparatively true to the previous study where most of the respondents were also female with mean overall satisfaction (mean 3.92) which signifies slightly satisfied/moderately satisfied (Huang et al, 2023).…”
Section: Discussionsupporting
confidence: 46%
“…Contrary to a previous study (Suresh and Kodikal, 2015), this study showed age group had no influence on job satisfaction (p>0.05). In terms, of gender majority of the respondents were female (mean rank=350.96) and moderate level of job satisfaction comparatively true to the previous study where most of the respondents were also female with mean overall satisfaction (mean 3.92) which signifies slightly satisfied/moderately satisfied (Huang et al, 2023).…”
Section: Discussionsupporting
confidence: 46%
“…A recent study conducted in Taiwan found that workrelated burnout and patient-related burnout negatively impacted job satisfaction [39]. Personal burnout may stem from various factors, including a lack of control over work, low job satisfaction, and an imbalance between work and personal life.…”
Section: Discussionmentioning
confidence: 99%
“…En el campo de la psicología organizacional, la satisfacción laboral es descrita como una actitud emocional positiva o complaciente que surge de la experiencia en el trabajo (Mason y Griffin, 2002). El bienestar organizacional es un concepto dinámico y multidimensional que engloba las expectativas, valores, entorno laboral y características personales de los empleados (Huang et al, 2023). Según De Ruijter et al ( 2023), la baja satisfacción laboral está asociada con efectos negativos tanto en la salud de los trabajadores como en el rendimiento de la organización.…”
Section: Clima Organizacional Y Satisfacción Laboralunclassified